2019
DOI: 10.1136/bmjopen-2018-026871
|View full text |Cite
|
Sign up to set email alerts
|

Opioid use disorder in chronic non-cancer pain in Germany: a cross sectional study

Abstract: ObjectivesThe DSM-5 diagnosis ‘opioid use disorder’ (OUD) was established to better describe and detect significant impairment or distress related to opioid use. There is no data on rates of OUD in chronic non-cancer pain (CNCP) in European countries. Therefore, our objective was to screen patients in specialised pain centres for signs of OUD.DesignCross-sectional questionnaire study.SettingFour outpatient pain clinics in the area of Bonn, Germany.Participantsn=204 patients participated in the study (response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 21 publications
1
13
0
8
Order By: Relevance
“…The prevalence of at least one opioid prescription within the last 12 months (3.5%) is lower than that reported in other studies (4.1%) and is most likely related to the lower age and therefore lower prevalence of chronic pain in ESA 2015 participants [19] Several studies from non-European countries have assessed the proportion of pOUD in populations with chronic pain which were similar to our results. They ranged between 21%, 23% and 41.3% in the USA as well as 20.8% in Australia and 26.5% in Germany [10,16,23,24]. Unfortunately, the ESA 2015 did not assess the presence of chronic pain nor the indication for, or duration of opioid pain therapy.…”
Section: Findings On Poud Prevalence From Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of at least one opioid prescription within the last 12 months (3.5%) is lower than that reported in other studies (4.1%) and is most likely related to the lower age and therefore lower prevalence of chronic pain in ESA 2015 participants [19] Several studies from non-European countries have assessed the proportion of pOUD in populations with chronic pain which were similar to our results. They ranged between 21%, 23% and 41.3% in the USA as well as 20.8% in Australia and 26.5% in Germany [10,16,23,24]. Unfortunately, the ESA 2015 did not assess the presence of chronic pain nor the indication for, or duration of opioid pain therapy.…”
Section: Findings On Poud Prevalence From Other Studiesmentioning
confidence: 99%
“…Still, there is little data with a focus on diagnosing addiction or misuse in patients receiving prescription opioids. Two recent, cross-sectional trials in Germany showed that a significant proportion of ambulatory patients with CNCP and long-term opioid therapy (LTOT) were at high risk of opioid misuse (31.5%) or had been diagnosed with prescription opioid use disorder (pOUD) (26.5%), yet both trials lacked in size and generalizability [10,11]. Additional analysis from larger datasets would be useful to assess the situation in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…25 Epidemiological data suggest that opioid misuse is also a concern in Europe. [26][27][28] In 2017, the six countries with the highest opioid consumption (reported as defined daily doses per million inhabitants per day) were, in order, the US, Germany, Canada, Austria, Belgium, and Switzerland. 28 To control the opioid crisis, guidelines currently recommend against the use of opioids to manage chronic pain.…”
Section: Management Of Chronic Painmentioning
confidence: 99%
“…OUD is difficult to diagnose in patients with chronic pain on LTOT because the current diagnostic criteria (Box 2) will often lead to a diagnosis of at least mild opioid use disorder in almost everyone. 42 Furthermore, it can be difficult to obtain the information to diagnose more moderate-Box 2 Diagnostic criteria for opioid use disorder 43 • Opioids are often taken in larger amounts or over a longer than intended. to-severe OUD as patients may not be forthcoming due to a variety of reasons including shame, and their own perceptions and understanding of how much their pain is contributing to their issues as opposed to their opioids.…”
Section: Potential Harms Associated With Standardised or 'Forced' Opimentioning
confidence: 99%